Fabrication of Biomembrane from Banana Stem for Lead Removal - Afianti Sulastri; Lena Rahmidar (Universitas Pendidikan Indonesia, 2016)
Heavy metal (i.e. lead (Pb)) is one of the environmental issues recently due to its danger for human health. Therefore, strategy for removing Pb from waste water treatment is important. One of the prospective methods to remove Pb is membrane biofilter. Here, the purpose of this study was to prepare the membrane biofilter for Pb removal process. In this study, membrane biofilter was produced from banana stem. Banana stem was selected because of its abundant availability in Indonesia. And, for somewhat, this banana stem can be environmental problems (become waste) since Indonesia is one of the top producers in the world. In short of the experimental procedure, we conducted three steps of experiments: (1) Preparation of microbial cellulose using Acetobacter xylinum using banana stem for a main source; (2) Synthesis of cellulose acetate; and (3) Preparation of biomembrane from obtained cellulose acetate. To produce membrane biofilter, the cellulose acetate was dissolved into dichloromethane to form a dope solution. Then, the doped solution was printed in Petri dish. Some biomembrane properties were characterized for identification, i.e. infrared spectra, electron microscope, and elemental analysis. Experimental results showed that we succeeded to prepare biomembrane with a pore size of 5 μm. The filtration efficiency of our prepared membrane was 93.7% of Pb when using Pb with a concentration of 10 ppm.